The development and function of the brain barriers – an overlooked consideration for chemical toxicity - Bell, Kiersten S.; O’Shaughnessy, Katherine L. (Frontiers in Toxicology, 2022)
It is well known that the adult brain is protected from some infections and toxic molecules by the blood-brain and the blood-cerebrospinal fluid barriers. Contrary to the immense data collected in other fields, it is deeply entrenched in environmental toxicology that xenobiotics easily permeate the developing brain because these barriers are either absent or non-functional in the embryo, fetus, and newborn. Here we review the cellular and physiological makeup of the brain barrier systems in multiple species, and discuss decades of experiments that show they possess functionality during embryogenesis. We next present case studies of two chemical classes, perfluoroalkyl substances (PFAS) and bisphenols, and discuss their potential to bypass the brain barriers. While there is evidence to suggest these pollutants may enter the developing and/or adult brain parenchyma, many studies suffer from confounding technical variables which complicates data interpretation. In the future, a more formal consideration of brain barrier biology could not only improve understanding of chemical toxicokinetics, but could assist in prioritizing environmental xenobiotics for their neurotoxicity risk.